Two new closely related species of Brongniartia (Fabaceae, Faboideae) from the Sierra Madre del Sur in Guerrero, México - Dorado, Óscar; Cruz-Durán Y., Ramiro; Bustamante García, Rubí (Phytotaxa, 2022)
Two species are described and illustrated of the state of Guerrero, México: Brongniartia alvarezii and B. variabilis (Fabaceae: Faboideae). They are similar to B. funiculata and B. abbottiae but have several distinguishing characteristics. All four species have relatively small flowers and grow in the temperate forest. Brongniartia alvarezii has yellowish white petals, something very rare on the genus, while B. variabilis has pink or pale pink standard and wings.